Penggunaan Metode Content Analysis dalam Penelitian Hadis - Andi Rahman (Qur'an and Hadith Academic Society, 2014)
To determine the authenticity of hadith, we need to analyze its chain of transmission and its content. The analysis of the chain of transmission is conducted through the data collection in the literature of tarajum al-ruwat, by analyzing the concept used in sanad criticism. Among the critique of hadith, some scholars used a concept generally used by others, but they understand it differently. Others use special concept not usually used by others, without explaining what they mean by that concept. There are also others who explain the biography of the hadith transmitters, without explaining their qualities, Al-Bukhari (d. 265 H) is among the ciritique of hadith who use these three concepts. This article, using content analysis methodology, tries to analyze and understand these three concepts.